Safe Performance of Peripheral Regional Anaesthesia: The Significance of Ultrasound Guidance. Issue 5 (October 2017) - Marhofer, P.; Fritsch, G.
Abstract : (Abstracted from Anaesthesia, 72(4):431–434, 2017) Ultrasound guidance has contributed toward making regional anaesthesia safer. Sermeus et al 1 ("Ultrasound-Guided Approach to Nerves [Direct vs. Tangential] and the Incidence of Intraneural Injection: A Cadaveric Study") evaluated the safety of ultrasound guidance in regional anaesthesia by comparing tangential and direct needle-to-nerve approach in nerve puncture and intraneural injection.